2018
DOI: 10.7150/ijms.23939
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Predicting Malignant Pleural Mesothelioma in a Mexican Population

Abstract: Background: Diagnosis of malignant pleural mesothelioma (MPM) remains a challenge, especially when resources in pathology are limited. The study aimed to evaluate cost-effective tumor markers to predict the probability of MPM in plasma samples in order to accelerate the diagnostic workup of the tissue of potential cases.Methods: We conducted a case-control study stratified by gender, which included 75 incident cases with MPM from three Mexican hospitals and 240 controls frequency-matched by age and year of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
4
15
0
Order By: Relevance
“…In previous studies, we have established an assay for the protein marker calretinin and confirmed the results in independent groups of patients from three continents, using a conventional case-control design 26 28 . These studies usually enroll patients with more advanced tumor stages and lack prediagnostic samples to assess the performance of markers to detect tumors prior to the occurrence of clinical symptoms 25 .…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In previous studies, we have established an assay for the protein marker calretinin and confirmed the results in independent groups of patients from three continents, using a conventional case-control design 26 28 . These studies usually enroll patients with more advanced tumor stages and lack prediagnostic samples to assess the performance of markers to detect tumors prior to the occurrence of clinical symptoms 25 .…”
Section: Introductionsupporting
confidence: 54%
“…Previously, we have tested a combination of calretinin and mesothelin using case-control studies that included symptomatic MM patients, thus with tumors at later stages of development 27 , 28 . Comparing the more sensitive of the two markers with their combination, the increase in sensitivity was relatively small in the Australian/German (14%) and the Mexican study groups (about 13%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the positive immunohistochemical MM markers that can discriminate between malignant and mesothelial cells with the highest sensitivity and specificity are calretinin, cytokeratin5/6, and WT1 [76]. As biomarkers that would enable an earlier noninvasive diagnosis of MM are widely studied, recent studies evaluated if soluble calretinin could also be used as a biomarker in MM [75,[77][78][79][80].…”
Section: Calretininmentioning
confidence: 99%
“…Studies showed that calretinin was increased in plasma and serum of MM patients compared to patients with other asbestos-related diseases and healthy controls [75,79,80]. Interestingly, patients with asbestosis also had slightly higher serum calretinin compared to patients with pleural plaques [75].…”
Section: Calretininmentioning
confidence: 99%